Qualidade fisiológica das sementes de feijão (Phaseolus vulgaris L) colhidas em diferentes períodos após a fecundação do óvulo - da Silva, Claudio Manuel; Vieira , Clibas; Sigueyuki Sediyama , Carlos (Revista Ceres, 2025)
A study was carried out in Viçosa with the bean (Phaseolus vulgaris L.) variety ’Rico 23’ to determine the physiological maturation, germination and vigor of seeds harvested in different periods after ovule fertilization. Floral buds were tagged and their pods were harvested after ovule fertilization at 48 hour intervals during 60 days. Ovule fertilization was considered to take place during flower opening.